26.A. Workshop: Assessing the role of policies and actions to address childhood obesity. (30th September 2020) - ,; ,
Abstract:  : Childhood obesity has grown to become one of the most dramatic features of the global obesity epidemic, with long-term consequences. The spread of obesity has been fueled by changes in social norms and living environments that have shaped individual behaviours making them conducive to excessive and imbalanced nutrition, sedentary lifestyles, and ultimately obesity and associated diseases. The STOP project will aim to generate scientifically sound, novel and policy-relevant evidence on the factors that have contributed to the spread of childhood obesity in European countries and on the effects of alternative technological and organisational solutions and policy options available to address the problem. STOP will translate the evidence gathered and generated into indicators and measurements, policy briefs and toolkits and multi-stakeholder frameworks. A special focus of STOP is understanding the stakeholders' networks and drivers of stakeholders' action. STOP will establish new ways for policy-relevant evidence to be generated, made available and used in the design and implementation of effective and sustainable solutions for childhood obesity at the EU, national and local levels. Each of the policy work packages will: Produce evidence syntheses and impact simulations for different policy approaches; Assess selected policy approaches and actions in children cohorts and other relevant settings; Devise policy toolkits and policy guidance to support the adoption and implementation of specific actions by relevant actors; Establish a country-based European accountability and monitoring framework in each policy area. The workshop aims to: Showcase the impact of different policy options evaluated throughout the STOP project; Increase participants' understanding and awareness of the opportunities and challenges associated with the implementation of selected policies; Increase awareness of public health professionals of the importance of overcoming siloes in identifying and implementing public health policies; Increase the understanding of multi-stakeholder engagement. The discussion will explore the role of stakeholders across different policy areas. We will explore the different definitions of "stakeholders" and "multi-stakeholders" engagement. This will also be an opportunity to explore some of the benefits, risks and challenges around stakeholder engagement, and explore what are the different types of stakeholders involved in these policies as well as their roles. The workshop will offer an opportunity to: Inform participants about existing physical activity, regulatory and fiscal policies to address childhood obesity; Inform participants about new, innovative EU-level projects that aim to address childhood obesity; Outline preliminary findings of the STOP project with regards to the effectiveness of the evaluated policies; Identify some of the gaps and limitations of existing policies and discuss some of the steps to ensure successful policy implementation. Key messages: Present new evidence on what policy approaches work in addressing key determinants of childhood obesity. Showcase findings on the attitudes of different stakeholders towards obesity policies, and debate the benefits, risks and challenges of multi-stakeholder engagement.